A review: natural polymer based hydrogel wound dressings in the wound healing of diabetics’ patients - Proma, Manjila Saliha (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.